2013
DOI: 10.1186/1478-7954-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Mortality following the Haitian earthquake of 2010: a stratified cluster survey

Abstract: IntroductionResearch that seeks to better understand vulnerability to earthquakes and risk factors associated with mortality in low resource settings is critical to earthquake preparedness and response efforts. This study aims to characterize mortality and associated risk factors in the 2010 Haitian earthquake.MethodsIn January 2011, a survey of the earthquake affected Haitian population was conducted in metropolitan Port-au-Prince. A stratified 60x20 cluster design (n = 1200 households) was used with 30 clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
0
31
0
1
Order By: Relevance
“…It is estimated that 3.5 million people were initially affected by the earthquake, more than 200,000 people were killed, and approximately 300,000 injured. 6,7 The stage was set in a country with limited capacity for response and a major natural disaster which placed high demands on regional and global responses. Haiti represents an appropriate contextual setting to discuss the stages of disaster response and the framework of capacity building.…”
Section: Haiti-the Earthquakementioning
confidence: 99%
“…It is estimated that 3.5 million people were initially affected by the earthquake, more than 200,000 people were killed, and approximately 300,000 injured. 6,7 The stage was set in a country with limited capacity for response and a major natural disaster which placed high demands on regional and global responses. Haiti represents an appropriate contextual setting to discuss the stages of disaster response and the framework of capacity building.…”
Section: Haiti-the Earthquakementioning
confidence: 99%
“…Approximately 1.5 million people were left homeless, and more than 3 million persons were affected. The earthquake left a devastated city, a collapsed hospital, and a recovery process with a cost of more than $4 billion [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the seven studies that found the elderly to be at higher risk for injury and death, Chou et al from Taiwan (2004) had the highest odds ratio for increased risk of death of 5.5 (95 % CI 4.4, 6.8). Three studies from the USA and Haiti (Mahue-Giangreco et al 2001;Peek-Asa et al 2003;Doocy et al 2013) found lower odds ratios of increased risk of injury OR 2.69 (95 % CI 1.34, 5.4), OR 2.9 (95 % CI 1.2, 7.4) and increased risk of death OR 2.8 (95 % CI 1.66, 4.72), respectively. Two other studies from Taiwan and China (Liang et al 2001;Dong et al 2012) also found age to be significantly associated with higher mortality and reported coefficient value of 0.101 (95 % CI 0.076, 0.125) and B coefficient of 1.539 (95 % CI N/A).…”
Section: Individual and Household Characteristics And Earthquake-indumentioning
confidence: 99%
“…Studies from the USA, Taiwan, Turkey and Haiti found no differences in the risk of injury and death by gender (Mahue-Giangreco et al 2001;Liang et al 2001;Ellidokuz et al 2005;Doocy et al 2013). Among the four studies that found women at higher risk of injury and death, two from the USA (Shoaf et al 1998;Peek-Asa et al 2003) had the highest odds ratios (OR) for increased risk of injury of 1.64 (95 % CI N/A) and 2.4 (95 % CI 1.2, 5.1), respectively.…”
Section: Individual and Household Characteristics And Earthquake-indumentioning
confidence: 99%
See 1 more Smart Citation